2013
DOI: 10.1111/pme.12057
|View full text |Cite
|
Sign up to set email alerts
|

Swim Therapy Reduces Mechanical Allodynia and Thermal Hyperalgesia Induced by Chronic Constriction Nerve Injury in Rats

Abstract: Objective Neuropathic pain is common and often difficult to treat because it generally does not respond well to the currently available pain medications or nerve blocks. Recent studies in both humans and animals have suggested that exercise may induce a transient analgesia and reduce acute pain in normal healthy individuals. We examined whether swim therapy could alleviate neuropathic pain in rats. Design Rats were trained to swim over a two week period in warm water. After the rats were trained, neuropathic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
39
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 46 publications
(41 citation statements)
references
References 72 publications
0
39
0
2
Order By: Relevance
“…Swimming provides positive results as a therapy for induced nerve injury in rats, reducing both mechanical allodynia and thermal hyperalgesia (Shen et al, 2013). In addition, swimming reduces pain hypersensitivity in a number of experimental models, including formalin and nerve injury-induced animal models of persistent pain, decreasing nerve injury, induced cold allodynia, thermal hyperalgesia in rats, and decreased nerve injury-induced hyperalgesia in mice (Kuphal et al, 2007).…”
Section: Experimental Studies Of Neuropathic Pain and Exercisementioning
confidence: 99%
“…Swimming provides positive results as a therapy for induced nerve injury in rats, reducing both mechanical allodynia and thermal hyperalgesia (Shen et al, 2013). In addition, swimming reduces pain hypersensitivity in a number of experimental models, including formalin and nerve injury-induced animal models of persistent pain, decreasing nerve injury, induced cold allodynia, thermal hyperalgesia in rats, and decreased nerve injury-induced hyperalgesia in mice (Kuphal et al, 2007).…”
Section: Experimental Studies Of Neuropathic Pain and Exercisementioning
confidence: 99%
“…However, forced exercise is highly stressful [30; 54; 70; 81; 104; 108], thus confounding the analgesic effects of exercise with the known analgesic effects of stress [115]. Similar to forced running, forced swimming effectively reduces persistent hypersensitivity [67; 139]; however, it too has long been considered a potent stressor producing opioid-dependent stress-induced analgesia [11; 21; 113; 147; 148]. Therefore, the opioid-dependent analgesic effects of forced exercise paradigms may be due at least in part to stress.…”
Section: Physical and Social Environment Affects Chronic Pain In Rmentioning
confidence: 99%
“…16,17 Among the various exercise modalities (treadmill, voluntary wheel running and swimming) used for studying the physiological response to exercise in rat models, swimming has an advantage as it utilizes a natural ability of rats. 16 Several studies on animal models have reported benefits of swimming exercise on preventing tumor growth and progression, pregnancy-associated longterm memory impairment and neuropathic pain caused by nerve injury; [18][19][20] however, data on benefits of swimming on ED are scarce. A recent study on rats found that regular exercise may help in improving penile erection by increasing penile neurotransmitter activity.…”
Section: Introductionmentioning
confidence: 98%